Limits on inelastic dark matter from ZEPLIN-III - Akimov,DY; Araujo,HM; Barnes,EJ; Belov,VA; Bewick,A; Burenkov,AA; Cashmore,R; Chepel,V; Currie,A; Davidge,D; Dawson,J; Durkin,T; et al. (Physics Letters B, 2010)
We present limits on the WIMP–nucleon cross section for inelastic dark matter from a reanalysis of the2008 run of ZEPLIN-III. Cuts, notably on scintillation pulse shape and scintillation-to-ionisation ratio, givea net exposure of 63 kg day in the range 20–80 keV nuclear recoil energy, in which 6 events are observed.Upper limits on signal rate are derived from the maximum empty patch in the data. Under standard haloassumptions a small region of parameter space consistent, at 99% CL, with causing the 1.17 ton yr DAMAmodulation signal is allowed at 90% CL: it is in the mass range 45–60 GeVc−2 with a minimum CLof 87%, again derived from the maximum patch. This is the tightest constraint yet presented using xenon,a target nucleus whose similarity to iodine mitigiates systematic error from the assumed halo.